A 2D MOF-based artificial light-harvesting system with chloroplast bionic structure for photochemical catalysis. Issue 14 (30th March 2021) - Jiang, Zhong Wei; Zhao, Ting Ting; Zhen, Shu Jun; Li, Chun Mei; Li, Yuan Fang; Huang, Cheng Zhi
Abstract : A 2D MOF-based artificial light-harvesting system as chloroplast mimic with high solar spectrum efficiency and energy transfer efficiency shows high-efficiency photocatalytic activity towards artemisinin production. Abstract : Developing an efficient artificial light-harvesting system (ALHS) with high solar spectrum overlap, energy transfer efficiency and photocatalytic performance remains a key challenge to realize sustainable energy utilization. Inspired by nature, herein, a 2D ALHS, namely, 2D MB/Yb-TCPP-SO4 nanosheets with chloroplast bionic structure were successfully constructed by coupling a kind of porphyrin-based 2D lanthanide metal–organic framework (namely, Yb-TCPP MOF) and methylene blue (MB). The newly assembled 2D ALHS showed 100% spectrum efficiency in the visible light region and high-efficiency energy transfer (up to 78.6%) between 2D Yb-TCPP nanosheets and MB. Significantly, this 2D ALHS possessed high activity towards the photocatalytic semi-synthesis of artemisinin after installing Brønsted acid sites, giving a record yield as high as 85%. This demonstrated that the as-constructed 2D ALHS is an ideal artificial solar converter, which showed a promising application for photochemical catalysis.